ANALISIS PEMILIHAN UNIT PENGOLAHAN BIOLOGIS PADA IPAL DOMESTIK SOREANG, KABUPATEN BANDUNG - Luqman Mufid Musyary; Widyo Astono; Sarah Aphirta (Universitas Trisakti, 2023)
This study aims to design a household wastewater treatment facility that will serve the Soreang Subdistrict in the Bandung Regency. The Soreang Subdistrict area covers approximately 2,561 hectares. At the end of the planning period, this IPAL will cater to around 185,821 residents with a processing capacity of 19,500 cubic meters per day until the year 2041. The reference wastewater quality parameters for the planning include a BOD5 of 93.2 mg/L, COD of 98.1 mg/L, and TSS of 57.9 mg/L. The selection of wastewater treatment units at the Soreang IPAL is based on the efficiency of removing processed wastewater parameters and the standard limits of wastewater parameter loads for each treatment unit option. The chosen biological treatment unit is the Aerated Lagoon because it aligns with the characteristics of the treated wastewater and the availability of adequate land. The planned sequence of treatment units for the Soreang IPAL includes a collection well, bar screen, grit chamber, equalization tank, aerated lagoon, secondary clarifier, and sludge drying bed. The design of the Aerated Lagoon results in a volume of 43,060 cubic meters, with a retention time of 1.5 days. The required oxygen volume for this process is 151.8 kilograms per hour. The design projection for this IPAL indicates that the treated water will have a BOD5 of 9 mg/L, COD of 9.47 mg/L, and TSS of 2.33 mg/L, meeting the established quality standards.